An overview of the use of bacteriophages in the poultry industry: Successes, challenges, and possibilities for overcoming breakdowns - Abd-El Wahab, Amr; Basiouni, Shereen; El-Seedi, Hesham R.; Ahmed, Marwa F. E.; Bielke, Lisa R.; Hargis, Billy; Tellez-Isaias, Guillermo; Eisenreich, Wolfgang; Lehnherr, Hansjörg; Kittler, Sophie; Shehata, Awad A.; Visscher, Christian (Frontiers in Microbiology, 2023)
The primary contaminants in poultry are Salmonella enterica, Campylobacter jejuni, Escherichia coli, and Staphylococcus aureus. Their pathogenicity together with the widespread of these bacteria, contributes to many economic losses and poses a threat to public health. With the increasing prevalence of bacterial pathogens being resistant to most conventional antibiotics, scientists have rekindled interest in using bacteriophages as antimicrobial agents. Bacteriophage treatments have also been investigated as an alternative to antibiotics in the poultry industry. Bacteriophages’ high specificity may allow them only to target a specific bacterial pathogen in the infected animal. However, a tailor-made sophisticated cocktail of different bacteriophages could broaden their antibacterial activity in typical situations with multiple clinical strains infections. Bacteriophages may not only be used in terms of reducing bacterial contamination in animals but also, under industrial conditions, they can be used as safe disinfectants to reduce contamination on food-contact surfaces or poultry carcasses. Nevertheless, bacteriophage therapies have not been developed sufficiently for widespread use. Problems with resistance, safety, specificity, and long-term stability must be addressed in particular. This review highlights the benefits, challenges, and current limitations of bacteriophage applications in the poultry industry.